Pristane induced lupus mice as a model for neuropsychiatric lupus (NPSLE) - Yun, Yang; Wang, Xuejiao; Xu, Jingyi; Jin, Chenye; Chen, Jingyu; Wang, Xueru; Wang, Jianing; Qin, Ling; Yang, Pingting (Behavioral and brain functions, 2023)
Background The pristane-induced lupus (PIL) model is a useful tool for studying environmental-related systemic lupus erythematosus (SLE). However, neuropsychiatric manifestations in this model have not been investigated in detail. Because neuropsychiatric lupus (NPSLE) is an important complication of SLE, we investigated the neuropsychiatric symptoms in the PIL mouse model to evaluate its suitability for NPSLE studies. Results PIL mice showed olfactory dysfunction accompanied by an anxiety- and depression-like phenotype at month 2 or 4 after pristane injection. The levels of cytokines (IL-1β, IFN-α, IFN-β, IL-10, IFN-γ, IL-6, TNF-α and IL-17A) and chemokines (CCL2 and CXCL10) in the brain and blood–brain barrier (BBB) permeability increased significantly from week 2 or month 1, and persisted throughout the observed course of the disease. Notably, IgG deposition in the choroid plexus and lateral ventricle wall were observed at month 1 and both astrocytes and microglia were activated. Persistent activation of astrocytes was detected throughout the observed course of the disease, while microglial activation diminished dramatically at month 4. Lipofuscin deposition, a sign of neuronal damage, was detected in cortical and hippocampal neurons from month 4 to 8. Conclusion PIL mice exhibit a series of characteristic behavioral deficits and pathological changes in the brain, and therefore might be suitable for investigating disease pathogenesis and for evaluating potential therapeutic targets for environmental-related NPSLE.